Dmitri Shostakovich’s Early Works: An Insight into the Creative Process through the Prism of Variants of Musical Works - Anton V. Lukyanov (Современные проблемы музыкознания)
The quantity of draft autographs pertaining to Dmitri Shostakovich’s early works is relatively small. But for acquiring a perception of the creative process of the young composer, other documents of this period may be used — variants of compositions that have been preserved in large quantities. And although some of them present simple complimentary authorial copies meant to be gifts for friends and acquaintances, differing to a minimal amount from the initial musical texts, there exists a number of variants where the composer’s creative will is distinctly manifested — an improvement of the perception of form and the sound of the musical composition. The article makes use of the method of comparative analysis of autograph scores, and all the variants were classified in to 1) compositional and 2) those connected with orchestration. The existent mixed variants, for the most part characteristic for later and more large-scale compositions (the opera Lady Macbeth of the Mtsensk District and the Eighth Symphony) have remained beyond the sphere of this research. The compositional transformations are examined on the example of two short pieces written during the year of the composer’s enrollment in the Petrograd Conservatory (1919). They demonstrate various diametrically opposed to each other techniques of work with the material: those include the omission of measure units and groups of measures and the additional composition of new musical text, at times, of great capacity. The variants connected with orchestration are examined on the example of Prelude No. 4 from the Eight Preludes opus 2. The piece has been orchestrated twice. It can be seen in the manuscripts how the composer gradually elucidates for himself the sound contours of the composition and correlates the orchestral profile with the form. The keen understanding of the regularities of orchestrating a composition for wind orchestra is reflected in the variants of the March from the incidental music for the performance of Vladimir Mayakovsky’s The Bedbug. As the result, it becomes possible to conclude that in the early period of his music, Shostakovich’s talent developed itself dynamically. The composer not only evaluates his own works critically, but also aspires to transform some of them. These transformations touch upon both the compositional and the timbral aspects of the compositions, however, at the same time, they do not bring in any radical changes, do not affect the figurative qualities or the musical language and preserve the general structure of the pieces. At the same time, the application of discrepant principles of transcription in various cases demonstrates the composer’s attention to the material.